2012
DOI: 10.1007/s13361-012-0504-x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer and Collision Induced Dissociation of Non-Derivatized and Derivatized Desmosine and Isodesmosine

Abstract: Abstract. Electron transfer dissociation (ETD) has attracted increasing interest due to its complementarity to collision-induced dissociation (CID). ETD allows the direct localization of labile post-translational modifications, which is of main interest in proteomics where differences and similarities between ETD and CID have been widely studied. However, due to the fact that ETD requires precursor ions to carry at least two charges, little is known about differences in ETD and CID of small molecules such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…the precursor charge state. [44,45] Meanwhile, literature reported that 100 ms were required for doubly sodiated glycerophosphocholine based lipids, [30] or doubly protonated (iso)desmosine, [29] 120-160 ms for doubly cationizated neutral oligosaccharides [31] or 100 and 150 ms for doubly and triply protonated chiral pentenoic amides. [28] Finally, we conclude that reaction times were lower for 3+ to 6+ with our cyclic polycationic carbohydrates than those commonly set for other described compounds.…”
Section: Precursormentioning
confidence: 99%
See 1 more Smart Citation
“…the precursor charge state. [44,45] Meanwhile, literature reported that 100 ms were required for doubly sodiated glycerophosphocholine based lipids, [30] or doubly protonated (iso)desmosine, [29] 120-160 ms for doubly cationizated neutral oligosaccharides [31] or 100 and 150 ms for doubly and triply protonated chiral pentenoic amides. [28] Finally, we conclude that reaction times were lower for 3+ to 6+ with our cyclic polycationic carbohydrates than those commonly set for other described compounds.…”
Section: Precursormentioning
confidence: 99%
“…Initially, ETD has been developed to preserve labile post translational modifications of proteins and furthermore to increase fragmentation efficiency of multiply charged whole protein during ESI-MS n analysis. [25,26] Nevertheless, ETD potential has been sporadically applied to other molecules such as synthetic polymers, [27] combinatorial chemistry end products, [28] pyridinium-based amino acid analogs (desmosine and isodesmosine), [29] crosslinking elastin [29], or also glycerophosphocholine lipids. [30] Few studies report the use of ETD for carbohydrate analysis and concerning exclusively neutral structures like milk oligosaccharides, [31] maltodextrin pentamer [32] or lacto-N-fucopentaose/difucohexaose.…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation of the singly charged precursor ion at 40 eV leads to a complex tandem mass spectrum in which DES and IDES show the same fragment ions that only differ in their relative intensities (Figure 2). Fragmentation is mainly characterized by the combined neutral losses of NH 3 and CO (sum of 45.0214 u) from one of the four aliphatic chains and the dissociation of the C ε -N bond of the residual Lys chain at the pyridinium nitrogen [28]. The most abundant peaks in the fragment spectra are a result of the combination of these processes.…”
Section: Collision-induced Dissociation Of Des and Idesmentioning
confidence: 99%
“…Baker and coauthors have described the dissociation of pyridiniumderivatized peptides, which is mainly driven by chargeremote processes [27]. It has been furthermore reported that CID of the doubly charged free amino acids is generally characterized by the loss of small molecules such as NH 3 and CO as well as the break between aliphatic chain and pyridinium nitrogen [28].…”
Section: Introductionmentioning
confidence: 99%
“…ETD has the conspicuous advantage of less sequence dependence on the cleavage sites and preservation of otherwise labile post‐ translational modifications, such as phosphorylation and glycosylation . In recent years, ETD has been successfully applied to evaluate the structural characterization of glycerophosphocholine lipids, oligosaccharides and desmosine and its isomer, isodesmosine . However, ETD requires precursor ions to form at least two positive charges, which limits its application in the study of small molecules such as steroids.…”
Section: Introductionmentioning
confidence: 99%